Raising the bar: Causal evidence on gender differences in risk-taking from a natural experiment - René Böheim; Mario Lackner; Wilhelm Wagner (Johannes Kepler University of Linz, Department of Economics, 2020)
We analyze data from top-tier professional athletes and find that female and male athletes differ in the timing and in the extent of their reactions to a change of the rules which increased the risk of failure. Male athletes increased risk-taking in the more risky environment immediately after the changes. Female athletes, however, increased risk-taking two years after the rule change. Over time, female athletes reverted to pre-reform risk-taking levels and male athletes' continued to make more risky decisions in the new environment. We attribute our findings to gender differences in competitiveness and risk preferences.
Keywords: J16; J44; 330; Competitiveness; risk-taking; gender differences